KONTRUKSI KEMAMPUAN PSIKOMOTORIK PESERTA DIDIK PADA PEMBELAJARAN FIQIH DI MAS AL HIKMAH - Ubaidillah Ubaidillah (Cross-border, 2023)
This study reveals a problem about how teachers build students’ psychomotor abilities in fiqih learning at MAS Al Hikmah. The formulation of this problem is 1) How is the application of curriculum in jurisprudence learning in MAS Al Hikmah?, 2) What is the method of learning jurisprudence in MAS Al Hikmah?, 3) How is the development of psychomtoric abilities of students in learning jurisprudence in MAS Al Hikmah?. This research uses qualitative research methods and descriptive approaches. The subject of fiqh teacher research, as well as MAS Al Hikmah students. With interview, observation and documentation data collection techniques. And technical analysis of data using data reduction, data presentation, and data verification. From the findings of this research the first curriculum in MAS Al Hikmah already uses the 2013 curriculum, and uses three stages, namely 1) The planning stage, 2) The implementation phase, 3) The evaluation phase. Both fiqh learning methods have used the Lecture Method, Question and Answer Method, Practice Method, Roll Playying Method, Assignment Method. Third Development of Psychomotor Ability in Subjects of Fiqh in MAS Al Hikmah, Determining the purpose of the form of action, Analyzing the skills in detail, Practicing brief explanation skills, Giving students the opportunity to try, Doing pr actice with supervision and guidance, Providing an assessment of students' efforts.